Report of One Year Follow up of Patients after TLIF using a 3-Dimensional Expandable Cage for Lumbar Fusion with Lordotic Correction. Issue 1 (April 2016) - Morrison, Robert; Rigal, Julien; Le Huec, Jean Charles; Schnake, Klaus J.
Introduction: The use of a new 3 dimensional (3D) expandable cage for TLIF was extensively studied in biomechanical tests, cadaver specimens and preliminary clinical series. A wide footprint is achieved through a one side portal due to the articulated implant positioned in the anterior third of the disc space. The lordotic correction is accomplished due to the expansion of the device in place assisting on the overall sagittal alignment. Previous reports presented showed initial promising clinical results. One year follow up of the first 10 patients is now reported. Material and Methods: Ten patients were included in a 12 months prospective review after a TLIF using a 3D Titanium alloy FLXFit expandable cage. The procedure was done for a single or two level fusion with positioning of the cage under fluoroscopy and expansion for disc space height and lordotic correction. All patients were supplemented with posterior instrumentation. Primary clinical outcomes were evaluated by preoperative, 6 months, 12 months and last follow-up visual analog scale (VAS) and the Oswestry Disability Index (ODI) scores. Complications and neurological impairment were recorded. Radiographic assessment of pre and post-operative results was performed with measurement of correction achieved in the frontal and sagittal planes with EOS imaging technology avoiding any distortion on X-Rays. All patients underwent CT scan control at 12 months. Results: All ten patients underwent a successful one or two levels instrumented TLIF without any permanent neurological, vascular or visceral complication. The 3D cage implantation provided lordosis augmentation of 8° (± 2.1°) allowing restoration of the sagittal alignment according to pre-op planning. On early post-op CT scans, good footprint and no endplate violation were shown with no cage subsidence. Clinical outcomes showed significant improvement for both VAS and Oswestry scores ( P < 0.05), 3.7 (± 2.9) and 31% (±11) respectively. Similar outcomes were found at 12 months: no cage subsidence, VAS and Oswestry scores ( P < 0.05), 3.5 (± 2.7) and 28, 4% (±12) respectively. Conclusion: Lumbar interbody fusion using this new 3D expandable cage provided correction of the lordosis in a shorter and effective surgical procedure. A wide footprint well positioned cage, with customized height and angular correction achievement assured an optimal load transmission and biomechanical environment for fusion. Initial clinical results were followed with successful clinical outcomes in all patients.